Analisis Yuridis Tindak Pidana Korupsi yang Dilakukan oleh Jaksa Pinangki - Azalya Kyla Saffanah Senok (Jurnal Riset Ilmu Hukum, 2022)
Abstract. Corruption occurs due to the existence of technological advances and innovations. according to history if a country goes through some rapid developments then it will also cause a greater need and desire for its people to commit the criminal act of corruption. A person who committed the criminal act of corruption needs to be given a penalty that causes an effect of deterrence while at the same time obligating said person into returning all the things they acquired from committing said crime. This research’s aim is to analyze regarding the criminal act of corruption that was committed by a prosecutor Pinangki. This research uses qualitative method where results of court judgement by the judge will be analyzed by connecting it to law theories applied in Indonesia. The judge sentenced the penalty of imprisonment and fine because there were two types of primary punishments sentenced imperatively, imprisonment and fine. Law is very closely related with justice, therefore there are many opinions stating that law has to be one with justice because law has a purpose in achieving justice for the people involved including the defendant. In this case the judge sentenced an imprisonment for 4 (four) years and a fine in the amount of Rp. 600.000.000 (six hundred million Rupiah) because the appeal decision that was based on the consideration of the first and third indictment’s sentences can be combined because the fact that both of them are based on the same primary crime. Abstrak. Korupsi terjadi dikarenakan adanya kemajuan dan inovasi teknologi, menurut sejarah apabila terjadi perkembangan pembangunan yang pesat di suatu negara maka semakin besar juga kebutuhan dan keinginan seseorang untuk melakukan tindak pidana korupsi Orang yang melakukan tindak pidana korupsi harus diberikan sanksi yang mengakibatkan efek jera dan diwajibkan untuk mengembalikan apa yang telah ia ambil. Sehingga penelitian ini menganalisis tentang tindak pidana korupsi yang dilakukan oleh Jaksa Pinangki. Metode penelitian ini menggunakan kualitatif dimana menganalisis hasil dari putusan yang telah ditetapkan Oleh hakim yang dihubungkan dengan teori-teori hukum yang berlaku di Indonesia. Hakim menjatuhkan saksi pidana penjara dan pidana denda dikarenakan terdapat penjatuhan dua jenis pidana pokok yang bersifat imperatif, yaitu antara pidana penjara dengan pidana denda, hukum memiliki keterkaitan dengan keadilan sehingga menurut banyak pendapat bahwa hukum harus digabungkan dengan keadilan, karena tujuan hukum adalah tercapainya rasa keadilan bagi masyarakat ataupun bagi terdakwanya. Dalam kasus ini penjatuhan sanksi yang diberikan oleh hakim sebanyak 4 (empat) tahun dan denda sebesar Rp.600.000.000 (enam ratus juta rupiah) dikarenakan putusan banding atas pertimbangan bahwa dakwaan kesatu dan dakwaan ketiga dapat digabungkan pemidanaanya dikarenakan satu pidana pokok.